2015
DOI: 10.1021/acs.macromol.5b01975
|View full text |Cite
|
Sign up to set email alerts
|

Allyl-Terminated Polypropylene Macromonomers: A Route to Polyolefin Elastomers with Excellent Elastic Behavior

Abstract: We report the design, synthesis, and physical/ mechanical properties of graft copolymers containing semicrystalline polypropylene side chains and amorphous ethylene/α-olefin copolymer backbones. These materials, a new class of semicrystalline, polyolefin-based thermoplastic elastomers, are made in two steps. First, allyl-terminated syndiotactic or isotactic polypropylene macromonomers are synthesized with controlled microstructure and molecular weight using bis(phenoxyimine)-titanium or chiral ansa-zirconocene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 43 publications
0
46
0
1
Order By: Relevance
“…Integrating these ordered microstructures in the atactic PP (aPP) or other amorphous copolymer will develop novel POEs with structural diversity and tunable properties, for example, sPP-b-poly(ethylene-co-propylene)-sPP triblock copolymer, iPP-b-aPP-block(b)-iPP multi-block copolymer, poly(ethylene-co-propylene)-graft(g)-iPP and poly(ethylene-co-propylene)-g-iPP copolymer. These new PP-based elastomers showed outstanding performance, including remarkable elastic properties, excellent stiffness-flexibility balance and easy processability [20][21][22]. With the development of group IV single-site catalysts, we can easily control the chain microstructure and the final material properties [23].…”
Section: Introductionmentioning
confidence: 99%
“…Integrating these ordered microstructures in the atactic PP (aPP) or other amorphous copolymer will develop novel POEs with structural diversity and tunable properties, for example, sPP-b-poly(ethylene-co-propylene)-sPP triblock copolymer, iPP-b-aPP-block(b)-iPP multi-block copolymer, poly(ethylene-co-propylene)-graft(g)-iPP and poly(ethylene-co-propylene)-g-iPP copolymer. These new PP-based elastomers showed outstanding performance, including remarkable elastic properties, excellent stiffness-flexibility balance and easy processability [20][21][22]. With the development of group IV single-site catalysts, we can easily control the chain microstructure and the final material properties [23].…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of PO-based block copolymers is currently highly topical. [33][34][35][36][37][38][39][40][41][42][43]…”
Section: Introductionmentioning
confidence: 99%
“…The subtle architecture of the PO chains is of particular interest in the bulk polyolefin industry. For example, sequence control to form olefin block copolymers (OBCs) is a formidable task in olefin polymerizations [1][2][3][4][5]. Following the commercialization of OBCs by the Dow Chemical Company [6][7][8], Coates et al recently reported the preparation of PE/iPP (iPP = isotactic polypropylene) multiblock copolymers to enhance capabilities of plastic recycling [1].…”
Section: Introductionmentioning
confidence: 99%